Toxicity of Beauveria bassiana to Bactrocera dorsalis and effects on its natural predators - Li, Xin-lian; Zhang, Jing-jing; Li, Dou-dou; Cai, Xin-yan; Qi, Yi-xiang; Lu, Yong-yue (Frontiers in Microbiology, 2024)
Entomopathogenic fungi (EPF) are economical and environmentally friendly, forming an essential part of integrated pest management strategies. We screened six strains of Beauveria bassiana (B1–B6) (Hypocreales: Cordycipitaceae), of which B4 was the most virulent to Bactrocera dorsalis (Hendel) (Diptera: Tephritidae). We further assessed the biological characteristics of strain B4 and the environmental factors influencing its ability to infect B. dorsalis. We also evaluated the effects of B4 on two of the natural predators of B. dorsalis. We found that strain B4 was the most virulent to 3rd instar larvae, pupae, and adult B. dorsalis, causing mortality rates of 52.67, 61.33, and 90.67%, respectively. B4 was not toxic to B. dorsalis eggs. The optimum B4 effects on B. dorsalis were achieved at a relative humidity of 91–100% and a temperature of 25°C. Among the six insecticides commonly used for B. dorsalis control, 1.8% abamectin emulsifiable concentrate had the strongest inhibitory effect on B4 strain germination. B4 spraying affected both natural enemies (Amblyseius cucumeris and Anastatus japonicus), reducing the number of A. cucumeris and killing A. japonicus adults. We found a valuable strain of EPF (B4) that is virulent against many life stages of B. dorsalis and has great potential for the biological control of B. dorsalis. We also provide an important theoretical and practical base for developing a potential fungicide to control B. dorsalis.